2022
DOI: 10.3390/ejihpe12020010
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Healthy Habits in University Students: A Comparative Associative Study

Abstract: There is evidence of increased psychopathology in university students and its relationship with unhealthy lifestyle habits. The objective of this work is to examine the prevalence and differences in psychopathological symptoms and lifestyle in a sample of university students according to educational levels and area of knowledge. A comparative associative study was conducted with 1405 university students. The results indicated significant differences in psychopathology and habits in the different groups. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…114,115 In one study, however, students from the sciences and arts and humanities had significantly higher mean levels of depression than students from health sciences and social sciences. 116 A study of nursing students in Spain and Chile found that levels of mental distress reduced over time, indicating that nursing education may be a protective factor against mental health disorders. 117 Therefore, peer support should be evaluated with students across various courses to understand any differences.…”
Section: Defining a Peermentioning
confidence: 99%
“…114,115 In one study, however, students from the sciences and arts and humanities had significantly higher mean levels of depression than students from health sciences and social sciences. 116 A study of nursing students in Spain and Chile found that levels of mental distress reduced over time, indicating that nursing education may be a protective factor against mental health disorders. 117 Therefore, peer support should be evaluated with students across various courses to understand any differences.…”
Section: Defining a Peermentioning
confidence: 99%
“…As noted in the National Framework for University Mental Health (Orygen, 2020), university settings play a key role in shaping and supporting students' mental health and wellbeing. Students can take a proactive role in protecting their mental health by engaging in simple strategies such as socialising with others, eating well, sleeping well, participating in physical activity, implementing study skills and practising emotion regulation-particularly in group contexts with other students (Dingle, Hodges, et al, 2021;Ruiz-Hernández et al, 2022). Students believe that teachers play an influential role in their wellbeing through being available and supportive and by demonstrating competence and passion for their work (Eloff et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this was consistent with the Mental Health dimension of the AQoL-8D, since a near significant interaction effect was observed in participants who consumed walnuts, which showed walnuts prevented a decline in mental health during the university examination period. Many studies have highlighted the growing problem of poor mental health in undergraduate students and a recent World Health Organisation Mental Health Survey found at least 75% of mental health disorders occur prior to 24 years of age [2][3][4]. Furthermore, a recent meta-analysis has also suggested that sleep is causally related to challenges in mental health with improvements in sleep reducing depression, anxiety and stress [43].…”
Section: Questionnairesmentioning
confidence: 99%
“…It can also contribute to certain metabolic disorders such as diabetes [1]. Many studies have highlighted the growing problem of poor mental health in undergraduate students as a result of the chronic nature of academic stress and a recent World Health Organisation Mental Health Survey found at least 75% of mental health disorders occur prior to 24 years of age, making undergraduate students particularly vulnerable to depression [2][3][4][5]. The association between chronic stress and depression may be due to the overuse or dysregulation of the stress response systems, namely the hypothalamicpituitary-adrenal (HPA) axis and sympatho-adrenomedullary system [6][7][8].…”
Section: Introductionmentioning
confidence: 99%